RESONATING ENVIRONMENTAL STEWARDSHIP THROUGH INTERPLAY OF LANGUAGE FUNCTIONS AND RHETORICAL DEVICES IN A PROTEST SONG - Bañez, Richard Mendoza (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
This case study, framed within a qualitative design, captured the interplay of language functions and rhetorical devices of a climate protest song in fostering sustainability through ecological conservation. This textual interplay identified through conducting a stylistic analysis of the lyrics of Ryan Cayabyab’s Paraiso, an Original Pilipino Music (OPM) climate protest song, illustrated the strategic use of language in making the students conscious of the prevailing environmental issues that drive them to engage in stewardship actions. This important role of language in music was affirmed by the thematic analysis of the responses of an incidental sample of 25 English as a Second Language (ESL) Filipino pre-service teachers on the ecocriticism-centred literary analysis guide questions after listening to the song. This finding encourages educators to view climate protest songs as a tool for promoting environmental literacy. This study calls for the integration of such songs in the ESL curricula to proactively engage students in the preservation of the environment while exploring the features of the English language.